An intelligent protection scheme for series-compensated transmission lines connecting large-scale wind farms - Prabhu, M. S.; Biswas, Sauvik; Nayak, Paresh Kumar; Abdelaziz, Almoataz; El-Shahat, Adel (Frontiers in Energy Research, 2023)
Series compensated transmission lines (SCTLs) are increasingly preferred for transmitting bulk amount of electricity generated from the present-day large-scale wind farm to the utility grid due to numerous technical and economic benefits. However, when a fault occurs in such wind farm integrated SCTL, the impedance across the metal oxide varistor protected series capacitor varies nonlinearly and also, the fault current contributed from the wind firm side is quite different compared to the grid side. Consequently, the widely used fixed impedance-based distance relaying schemes find limitation when used for protecting such crucial TLs. In this paper, the impacts of series compensation and wind farm integration on distance relay is investigated and proposes an intelligent relaying scheme using the current measurements only. In the proposed scheme, the fault detection task is performed using the signs of the half-cycle magnitude differences of the line end positive-sequence currents and the fault classification task is performed using only the local current measurements processed through the Fourier-Bessel series expansion (FBSE) bagging ensemble (BE) classifier. The non-stationary components present in the current signal at the initiation of a fault are captured by calculating FBSE coefficients, and the singular value decomposition is applied for dimensionality reduction of the feature set. Finally, the extracted features are used by BE classifier for fault classification. The method is evaluated in MATLAB/Simulink® on numerous fault and non-fault data simulated in 2-bus systems and also validated through OPAL-RT (OP4510) manufactured real-time digital simulation platform. The obtained results (response time for fault detection and classification <10 ms), including the comparative assessment results (fault detection accuracy =100% and fault classification accuracy =99.37%) justify the effectiveness of the proposed relaying scheme in protecting the wind farm integrated SCTLs.